2001
DOI: 10.1007/978-94-017-3674-9_41
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Wheat Plants: A Powerful Breeding Source

Abstract: Plant breeders are always interested in new genetic resources. In the past, the sources have been limited to existing germplasm. Genetic engineering now provides the opportunity for almost unlimited strategies to create novel resources. As a first stage, the Applied Biotechnology Center (ABC) at CIMMYT developed a method for the mass production of fertile transgenic wheat (Triticum aestivum L.) that yields plants ready for transfer to soil in 13-14 weeks after the initiation of cultures, and, over the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Romagosa et al (1996) found different QTL × E of adapted cultivars of some major crops (e.g. Koebner & Snape, 1999;Pellegrineschi et al, 2001;Horvath et al, 2002). The usefulness of these advancements, in the case of traits controlled by major genes or few genes, is evidenced by the number of transgenic crops grown in many regions.…”
Section: Identifying Useful Genes For Yield: Likelihood Inversely Relmentioning
confidence: 99%
“…Romagosa et al (1996) found different QTL × E of adapted cultivars of some major crops (e.g. Koebner & Snape, 1999;Pellegrineschi et al, 2001;Horvath et al, 2002). The usefulness of these advancements, in the case of traits controlled by major genes or few genes, is evidenced by the number of transgenic crops grown in many regions.…”
Section: Identifying Useful Genes For Yield: Likelihood Inversely Relmentioning
confidence: 99%
“…Bansi, an old Indian durum wheat cultivar, was reported as susceptible to A. triticina in the 1960s (Prabhu & Prasada, 1966). Wheat genotypes RR21 and Bobwhite SH9846, reported previously as susceptible (Sinha et al ., 1991; Chaurasia et al ., 1999, 2000; Pellegrineschi et al ., 2001), were found to be highly resistant to all A. triticina isolates used in this study. Alternaria alternata IMI 289680, MUCL 42372, MUCL 44262 and MUCL 45332, A. arborescens MUCL 42525, MUCL 44259, MUCL 44260, MUCL 44261 and MUCL 45333, and A. tenuissima MUCL 42464 and MUCL 42561 were found to be nonpathogenic on wheat, despite being collected from wheat samples showing leaf blight lesions apparently induced neither by the tan spot nor by the spot blotch pathogens, but alleged to be caused by A. triticina .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pellegrineschi et al . (2001) suggested that resistance to alternaria leaf blight in transgenic wheat plants might be increased by the antifungal activity of thaumatin‐like proteins from barley, a nonhost of A. triticina .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations